2019
DOI: 10.1007/s10476-019-0840-1
|View full text |Cite
|
Sign up to set email alerts
|

Johnson Pseudo-Contractibility of Certain Banach Algebras and Their Nilpotent Ideals

Abstract: In this paper, we study the notion of Johnson pseudo-contractibility for certain Banach algebras. For a bicyclic semigroup S, we show that ℓ 1 (S) is not Johnson pseudo-contractible. Also for a Johnson pseudo-contractible Banach algebra A, we show that A has no non-zero complemented closed nilpotent ideal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Note that the notion of Johnson pseudo-contractibility is stronger than pseudo-amenability and it is weaker than pseudo-contractibility. Furthermore the Johnson pseudo-contractibility of various classes of Banach algebras such as, semigroup algebras, Segal algebras and Lipschitz algebras have been studied [15,16] and [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the notion of Johnson pseudo-contractibility is stronger than pseudo-amenability and it is weaker than pseudo-contractibility. Furthermore the Johnson pseudo-contractibility of various classes of Banach algebras such as, semigroup algebras, Segal algebras and Lipschitz algebras have been studied [15,16] and [2].…”
Section: Introductionmentioning
confidence: 99%
“…A similar result has been given by Grønbaek and Habibian [12], also for a commutative semigroup S; they showed that 1 (S) is biflat if and only if S is a uniformly locally finite semi-lattice of an abelian group. In [2] the authors showed that 1 (S) is not Johnson pseudo-contractible, whenever S is a bicyclic semigroup or S is the semigroup (N, max). Pseudo-contractibility and Johnson pseudo-contractibility of uniformly locally finite inverse semigroups were characterized in [8] and [15], respectively.…”
Section: Introductionmentioning
confidence: 99%